SRSD in Writing and Professional Development for Teachers: Practice and Promise for Elementary and Middle School Students with Learning Disabilities. Issue 3 (9th July 2017) - Gillespie Rouse, Amy; Kiuhara, Sharlene A.
Abstract : In this article, we outline common challenges students with LD have with writing and then provide an overview of the evidence‐based Self‐Regulated Strategy Development (SRSD) instructional model in writing. Next, we provide detailed descriptions of SRSD instruction for students with LD in elementary and middle school classrooms, noting important considerations when planning for and implementing SRSD in these grades. We then address an emerging area of research, practice‐based professional development (PBPD) for SRSD. After providing descriptions of PBPD for SRSD, we summarize PBPD for SRSD studies and argue for continued research in this area. We provide our readers with rich descriptions of PBPD for SRSD, highlighting its promise for students with LD and their teachers.